2018
DOI: 10.4322/2357-9730.78285
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Cryptococcus neoformans by MALDI-TOF mass spectrometry in blood culture

Abstract: This is a report of isolation of Cryptococcus neoformans from blood culture. Identification was conducted by matrix-assisted laser desorption/ionization-time-of-flight mass spectrometry. The relevance of this report is related to the site affected, the severity of the infection, and the importance of correct and rapid identification of the causative pathogen for a successful treatment and for reducing the risk of morbidity and mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…The role of the susceptibility test result as a predictor for early or late clinical outcomes remains unclear. A previous study showed some correlation between fluconazole MICs and the poor prognosis of CM [ 4 , 11 , 20 ]. However, we did not observe such correlation in our study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The role of the susceptibility test result as a predictor for early or late clinical outcomes remains unclear. A previous study showed some correlation between fluconazole MICs and the poor prognosis of CM [ 4 , 11 , 20 ]. However, we did not observe such correlation in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Cryptococcus species were identified using matrix-assisted laser desorption ionization–time-of-flight mass spectrometry (MALDI-TOF MS) following the manufacturer’s recommendations [ 10 , 11 , 12 ].…”
Section: Methodsmentioning
confidence: 99%